In School and Out of Trouble? The Minimum Dropout Age and Juvenile Crime - Anderson, D. Mark (The Review of Economics and Statistics, 2014)
Abstract This paper examines the relationship between the minimum high school dropout age and juvenile arrest rates by exploiting state-level variation in dropout age laws. County-level arrest data for the period 1980 to 2008 and difference-in-difference-in-difference-type empirical strategy are used to compare the arrest rates over time of various age groups within counties that differ by their state's minimum dropout age. The evidence suggests that minimum dropout age requirements have a significant and negative effect on property and violent crime arrest rates for individuals 16 to 18 years old. The results are consistent with an incapacitation effect of schooling.